Pengembangan Investasi Modal Sosial dalam Pembangunan - Zulkifli Lubis (Antropologi Indonesia, 1999)
Development in Indonesia has been characterized by a top-down and centralistic model, placing importance upon economic capital and measured by economic growth. The author argues for the importance of developing social capital investment, whereby social capital is seen as the capacity that emerges from mutual trust in society and transmitted through cultural mechanism. He provides two contrasting cases of social capital investment in development: community-based management resource management in South Tapanuli and a Social Safety Net program in North Sumatera. Although both were designed to allow for equal participation in every stage of the program, the latter met with failure because of very high bureaucratic intervention and the absence of trust among participants. On the other hand, the former program proved successful for the opposite reasons, and for the added ability of the community in crafting institutions.